The deep time of the screen, and its forgotten etymology. Issue 1 (1st January 2019) - Avezzù, Giorgio
ABSTRACT: While "screen" is usually considered a word with a Nordic origin, its older and forgotten classical root shows that its semantic field is more curious than media archaeology commonly thinks. Above all, this proves the existence of a long-lasting connection between the screen and the act of seeing, and the very notion of spectacle in its broader sense. Such a different—Latin, Epicurean—etymology of "screen" can put the idea of separation at the heart of the concept of spectacle. From this perspective, the value of a spectacle stems from a vision of difference—the act of spectating being both detached and detaching, as it enables the spectators to take themselves out of the picture, and thus to draw a morale from what they regard as other than themselves. If we bring this understanding of "screen" to the field of film theory, we deal with an idea of experience that has less to do with the notion of engagement adopted by contemporary approaches focusing on affect, emotion, cognition (and neuroscience), and more to do with the disengagement of the spectator from whatever is represented, and even more to do with the added value that such disengagement brings forth.